A Survey of Nigerian Governments and the Conduct of Foreign Policy, 1960-1993 - Salami, B. Olawale (NIU Journal of Social Sciences, 2019)
Nigeria’s Foreign Policy over the years has vacillated from the legacy of conservatism inherited from Britain at independence in 1960 to a more dynamic Afrocentric foreign policy posture ushered in after the civil war between 1967 and 1970. The factors that gave rise to this include both internal and external forces that compel the country to change its foreign policy postures over the years. This paper examines the changing trend in Nigeria’s foreign policy since independence in 1960. It highlights the major issues and main foreign policy thrusts of various regimes in the country since 1960. The paper identified the major themes in the country’s foreign policy with a cursory analysis of the factors that gave rise to them. Drawing from its findings, the paper argued that Nigeria’s foreign policy like that of other countries in the international system is dynamic and responsive to internal and external changes. It concluded therefore that the country has come a long way in realising some of the objectives enumerated in its foreign policy thrust since independence in 1960.